2005
DOI: 10.1177/000313480507100301
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Early Enteral Feeding in Gastrointestinal Surgery: A Prospective Survey of 51 Consecutive Patients

Abstract: Early postoperative oral feeding has been demonstrated to be safe and not increase postoperative morbidity. There are conflicting reports about its effect on postoperative length of stay. Some patients will fail attempts at early postoperative feeding and may be relegated to a longer postoperative course. Few studies to date have attempted to identify cost savings associated with early oral support, and those identified address nasoenteric support only. Fifty-one consecutive patients were randomized into eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Nevertheless, it remains unclear whether vomiting and nasogastric reinsertion are more likely with early feeding. In this review, two RCTs found significant increase in both, but Lucha et al. (2005) noted only a non‐significant trend to greater nasogastric reinsertion.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, it remains unclear whether vomiting and nasogastric reinsertion are more likely with early feeding. In this review, two RCTs found significant increase in both, but Lucha et al. (2005) noted only a non‐significant trend to greater nasogastric reinsertion.…”
Section: Discussionmentioning
confidence: 69%
“…Types of surgical procedures were evenly matched between groups in all studies. Laparoscopic surgery was performed only in 1 study; in other studies, open surgery was performed . When reported, there was substantial heterogeneity between studies in the use of perioperative protocols, including use of epidural anesthesia, preoperative bowel lavage, nonsteroid anti‐inflammatory drugs, and opioids.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the nature of the intervention, blinding could not be applied in any study. Three studies gave no explicit description of the randomization method, resulting in an unclear risk of bias . One open‐label study used blocked randomization with a fixed block size of 6; hence, risk of selection bias was present .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations